Genetic characteristics of piliated Streptococcus pneumoniae serotype 35B, increased after introduction of pneumococcal vaccines in Japan - Miyazaki, Haruko; Shibuya, Rie; Chang, Bin; Inukai, Tatsuya; Miyazaki, Yoshitsugu; Ubukata, Kimiko; Nakamura, Shigeki; Matsumoto, Tetsuya (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2020)
Streptococcus pneumoniae is a commensal bacterium of the human nasopharynx and a major causative pathogen of bacterial diseases worldwide. Pilus of S. pneumoniae is one of the virulence factors which enhance the adhesion to the host epitherial cells in the upper respiratory tract. We analyzed the serotype distribution and presence of pilus genes, rrgC and sipA, among 785 S. pneumoniae isolates from specimens of patients with invasive or non-invasive disease in a regional Japanese hospital between October 2014 and August 2018. We next performed multilocus sequence typing and penicillin-resistant genotyping for 86 isolates of serotype 35B. Serotype 35B was the most frequent serotype which accounted for 11.0% of total isolates and had pilus genes at high rate (80.2%). Clonal complex (CC) 558 isolates accounted for 77.9% of serotype 35B and were highly positive for rrgC and gPRSP (98.5%). In contrast, all CC2755 isolates (19.8%) were rrgC-negative and gPISP. Our results suggest that CC558 may assist the prevalence of serotype 35B after the introduction of vaccines, as that clone has pili as adhesins in addition to non-susceptibility against penicillin. These results may be useful information for development of optimal preventive strategies. Continuous studies on serotype distribution and virulence factors of S. pneumoniae are necessary.